Variant Histology: The Impact on Oncological Outcomes of Patients with Urothelial Carcinoma of The Bladder Treated with Radical Cystectomy - Berk Hazır; Hakan Bahadır Haberal; Kadir Emre Baltacı; Parviz Shahsuvarli; Bülent Akdoğan; Cenk Yücel Bilen; Mustafa Sertaç Yazıcı (Journal of Urological Surgery, 2021)

(untitled)
Objective:To investigate the impact of variant histology (VH) of urothelial carcinoma (UC) of the bladder on oncologic outcomes after radical cystectomy (RC).Materials and Methods:We identified 125 patients with cT2-T4N0M0 UC who underwent RC without perioperative systemic therapy between 2014 and 2019 at a single tertiary care referral center. The Mann-Whitney U test and chi-square test were used to compare the statistically significant differences in medians and proportions, respectively. The Kaplan-Meier method and Cox regression analyses tested the effect of different VH on cancer-specific survival (CSS) and overall survival (OS).Results:Of 125 patients, 70 (56%) had pure UC, whereas 55 (44%) had VH. The mean patient age and the median follow-up were 63.6±9.7 years and 12.5 (3-72) months. The female to male ratio was 13/112. The presence of lymphovascular invasion, locally advanced stage (≥pT3), and recurrence status were significantly higher in patients with VH than those with pure UC. In all patients, the presence of VH was not significantly associated with the presence of lymph node (LN) metastasis. In the multivariable Cox regression analyses, the type of UC [hazard ratio (HR) 1.80, 95% confidence interval (CI) 1.00-3.24, p=0.050] and age (HR=1.050, 95% CI 1.016-1.086, p=0.004) was associated with the OS, whereas the LN metastases was associated the CSS (HR=2.962, 95% CI 1.456-6.027, p=0.003) and OS (HR=3.211, 95% CI 1.778-5.799, p<0.001).Conclusion:Our study demonstrated that VH in bladder cancer was associated with unfavorable clinicopathological features and a poorer OS prognosis. However, VH is not independently significant with the CSS. In addition, this study confirms that the LN metastasis represents a robust and independent predictor of inferior CSS and OS.